Plan-do-study-act (PDSA) interventions to improve real-world endoscopy unit productivity - Bradley, Christopher; Sumethasorn, Matt; Kim, Jin Sun; Wang, Sarah; Martinez, Leslie; Chang, Megan; Lemus, Lillian; Katebian, Behrod; Bruce, Dara; Lee, Andy; Baden, Rachel; Yee, Hal; Buxbaum, James (Endoscopy International Open, 2024)
Background and study aims The Plan-Do-Study Act (PDSA) ramp is a framework that uses initial small changes to build consensus and momentum for subsequent, iterative process improvement. Our aim was to study its impact on endoscopy unit efficiency and throughput.Methods Following a granular time-and-motion analysis to evaluate baseline performance (phase 1) we instituted successive interventions and measured their impact on core efficiency metrics including procedure volume and turnover time (phases 2–3).Results We identified that inefficiency in turnover of anesthesia-supported endoscopy was the most crucial issue. Implementation of a pre-procedure anesthesia visit in phase 2 reduced turnover time by 15.5 minutes (95% confidence interval 3.9–27.1 minutes). Subsequent changes (phase 3) including front-loaded procedure scheduling and parallel in-room preparation resulted in an 18% increase in procedure volume.Conclusions The PDSA ramp model is an effective means of assessing operational processes, developing novel interventions, and building consensus to improve the real-world productivity in a resource-conscious manner.
Keywords: Quality and logistical aspects; Preparation; Quality management; Performance and complications